2018
DOI: 10.1002/ptr.6063
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of Camellia sinensis (green tea): A review

Abstract: Many scientific articles proved that green tea (GT), Camellia sinensis, has a great potential to manage central nervous system, cardiovascular, and metabolic diseases and treat cancer and inflammatory disorders. However, it is important to consider that "natural" is not always "safe." Some relevant articles reported side effects of GT, detrimental effects on health. The aim of this study is to provide a classified report about the toxicity of GT and its main constituents in acute, subacute, subchronic, and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 132 publications
0
81
0
5
Order By: Relevance
“…From the human consumption perspective, the Food and Drug Administration currently recommends that the total daily consumption of l ‐THE should not exceed 1,200 mg/day for healthy adults. Additionally, these values are further supported by worldwide safe historical consumption of high quantities of GT containing l ‐THE (Bedrood, Rameshrad, & Hosseinzadeh, ; Graham, ).…”
Section: Physical Properties Pharmacokinetics and Toxicity Of L‐thementioning
confidence: 88%
“…From the human consumption perspective, the Food and Drug Administration currently recommends that the total daily consumption of l ‐THE should not exceed 1,200 mg/day for healthy adults. Additionally, these values are further supported by worldwide safe historical consumption of high quantities of GT containing l ‐THE (Bedrood, Rameshrad, & Hosseinzadeh, ; Graham, ).…”
Section: Physical Properties Pharmacokinetics and Toxicity Of L‐thementioning
confidence: 88%
“…The MTS assay showed a decrease of cancer cells viability cultured with both kinds of Pt NPs in comparison with the control; however, 13% and 16% larger decrease is observed for the SW480 and SW620 cells cultured with NPs synthesized by green chemistry. In the literature, anticancer properties of green tea have been reported, which are attributed to the presence of polyphenols, such as epicatechin, epigallocatechin, epicatechin‐3‐gallate, and epigallocatechin‐3‐gallate . Several studies have shown that drinking green tea can prevent carcinogenesis and the development of various types of cancers Moreover, green tea polyphenols are responsible for the regulation of different cancer‐related processes and factors, including DNA methylation and microRNA, histone, and protein modification .…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, anticancer properties of green tea have been reported, which are attributed to the presence of polyphenols, such as epicatechin, epigallocatechin, epicatechin-3-gallate, and epigallocatechin-3-gallate. [60,61] Several studies have shown that drinking green tea can prevent carcinogenesis and the development of various types of cancers [21,[62][63][64] Moreover, green tea polyphenols are responsible for the regulation of different cancer-related processes and factors, including DNA methylation and microRNA, histone, and protein modification. [65,66] Recently, it was shown that green tea plays a very important role in cancer prevention.…”
Section: Viability Changesmentioning
confidence: 99%
“…The published review articles highlight the potential of green tea and phytoestrogens in breast cancer prevention (Anandhi Senthilkumar, Fata, & Kennelly, ; Najaf Najafi, Salehi, Ghazanfarpour, Hoseini, & Khadem‐Rezaiyan, ; Xiao, Zhang, Tong, & Shi, ). Similarly, there is evidence in the literature that the consumption of both green tea and phytoestrogens‐containing vegetables could be correlated with a low incidence of other chronic pathologies, such as cardiovascular and metabolic diseases (Peluso & Serafini, ; Andrew & Izzo, ; Rietjens, Louisse, & Beekmann, ; Bedrood, Rameshrad, & Hosseinzadeh, ;).…”
mentioning
confidence: 92%